Differential Export Taxes along the Oilseeds Value Chain: A Partial Equilibrium Analysis. (1st April 2014) - Bouët, Antoine; Estrades, Carmen; Laborde, David
Abstract : Differential Export Tax (DET) rates, or the policy of imposing high export taxes on raw commodities and low export taxes on processed goods, generate public revenues and promote production at the more processed stages of a value chain. We study the theoretical justification of this trade policy by designing a simple international trade model which shows that a tax on exports of a raw agricultural commodity in a country that exports seeds and vegetable oils increases the sum of final consumers' surplus, processing sector profits, farmers' surplus, and public revenues. We then develop a partial equilibrium model of the world's oilseed value chain and simulate the total elimination of DETs in Argentina and Indonesia, as well as the independent removal of export taxes at various stages of production in the same countries. Estimations show that removing export taxes along the entire value chain in Argentina and Indonesia reduces the local production of biofuels by only 0.4% in Argentina, while eliminating only the export tax on biofuels in Argentina leads to a 9.6% volume increase in Argentinean biofuels production.